Self-determination theory and motivation for music. (September 2018) - MacIntyre, Peter D.; Schnare, Ben; Ross, Jessica
Learning the skills to be a musician requires an enormous amount of effort and dedication, a long-term process that requires sustained motivation. Motivation for music is complex, blending relatively intrinsic and extrinsic motives. The purpose of this study is to investigate the motivation of musicians by considering how different aspects of motivational features interact. An international sample of 188 musicians was obtained through the use of an online survey. Four scales drawn from Self-Determination Theory (intrinsic, identified, introjected, and extrinsic regulation) were utilized along with other motivational constructs, including motivational intensity, desire to learn, willingness to play, perceived competence, and musical self-esteem. To integrate the variables into a proposed model, a path analysis was conducted among the motivation variables. Results showed that the intrinsic motives are playing the major role in the maintenance of the motivational system, while extrinsic motives are less influential. Support was found for a feedback loop, whereby desire to learn feeds into increased effort at learning (i.e., motivational intensity), leading to the development of perceived competence, which is then reflected back into increasing desire to learn. Increases in these variables help to create a virtuous cycle of motivation for music learning and performance.